IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 15 TAHUN 2011 TENTANG PAJAK RESTORAN OLEH BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN HULU SUNGAI UTARA - Sugianor Sugianor (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
This research is aimed at the Office of Tax Management Board And Retribution of Hulu Sungai Utara Regency which is aimed to find out how the Implementation of Regional Regulation Policy Number 15 Year 2011 on Restaurant Taxes and any Factors that participate in implementing it. The research method used is descriptive-qualitative method, data completion process by observation, interview and documentation. With a robust sample of 12 people and data analysis techniques by means of data reduction, data presentation and withdrawal. The results of research conducted on the things that have been good by the relevant agencies, will other implementers who are not helped by not participating to achieve success by paying with premises on time and follow the procedures of the direction of a solid institution then it is appropriate as said successfully touched. However, the factors that are developing are: Standards and Policy Objectives that are still not in accordance with the region, Characteristics of Implementing Agencies not yet firm and Social and Political Condition not yet understand the society. Has not understood the people who are still unclear about this tax retribution system but the role of the agency and the government is to date still leads by providing information regularly about this restaurant tax even though it has been repeatedly described so that the restaurant can understand and understand to Pay the dues. More assertiveness by the agencies in the implementation of this regulation is needed so that the public can understand clearly and avoid the prevailing provisions, and apply the applicable judicial standards.